Redox and selective oxidation properties of Mn complexes grafted on SBA-15 - Saikia, Lakshi; Srinivas, D. (Catalysis Today, 2009)
Manganese complexes of 5,10,15,20-tetraphenylporphyrin (Mn(TPP)Cl) were grafted on SBA-15 functionalized with propyl-amine, -thiol and -sulfonic acid groups. The acido-basic properties of the support influenced the oxidation state, redox behavior and selective oxidation properties of the Mn complexes. Acidic supports (SBA-15-pr-SH and SBA-15-pr-SO(3)H) promoted the reduction of Mn ions in Mn-TPP complexes from 3+ to 2+ oxidation state. A similar behavior was found also when Mn(Salen)Cl complexes were immobilized on those supports. However, the extent of such facile reduction was more in the case of Mn-TPP than in Mn-Salen complexes. The former exhibited superior catalytic activity (turnover frequency) than the latter-type Mn complexes in regio-, stereo- and chemoselective oxidation of R-(+)-limonene with molecular oxygen (1 atm) at ambient temperatures. The catalytic oxidation activity correlates with the redox behavior of the grafted Mn complexes. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Grafted manganese complexes; Mn(Salen)Cl; Mn(TPP)Cl; Organo-functionalized SBA-15; Redox behavior of Mn; Selective oxidation of limonene